2013
DOI: 10.1007/s11581-013-0914-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sintering temperature and aging on properties of cermet Ni/8YSZ materials obtained by citric method

Abstract: The anode supported cell for solid oxide fuel cell, as a modification of the traditional Ni-YSZ anode supported on electrolyte, is examined in this work. The materials obtained on the base of citric method are presented and investigated in this work. The materials consisted of 40 wt.% Ni/YSZ, 50 wt.% Ni/YSZ and 60 wt.% Ni/YSZ were obtained. The base Ni/YSZ materials are tested on the two ways: (a) aging tests and (b) sintering tests. All the materials after aging and sintering are tested by the impedance spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For instance, Ni supported on zirconia (ZrO 2 ) doped with yttria (Y 2 O 3 ) (Ni/YSZ), is a suitable material for SOFCs as it has a high mixed electronic-ionic conductivity and high mechanical strength. 11 The key reactions in these devices occur at the triple phase boundary (TPB) where the gas phase, Ni particles and the YSZ surface meet. Therefore, tuning and stabilizing the Ni microstructure will affect the SOFC performance and electrode lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ni supported on zirconia (ZrO 2 ) doped with yttria (Y 2 O 3 ) (Ni/YSZ), is a suitable material for SOFCs as it has a high mixed electronic-ionic conductivity and high mechanical strength. 11 The key reactions in these devices occur at the triple phase boundary (TPB) where the gas phase, Ni particles and the YSZ surface meet. Therefore, tuning and stabilizing the Ni microstructure will affect the SOFC performance and electrode lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…349 For a 50% Ni-YSZ material fabricated by citric method TEC of 9.1 × 10 −6 K −1 was obtained in 5% H 2 + 95% Ar atmosphere. 353…”
Section: Solid Oxid Electrolysis Cell Componentsmentioning
confidence: 99%
“…349 For a 50% Ni-YSZ material fabricated by citric method TEC of 9.1 × 10 −6 K −1 was obtained in 5% H 2 + 95% Ar atmosphere. 353 The electrical conductivity is partly inuenced by the particle size of the material, the porosity, the volume fraction of Ni, the distribution of Ni and YSZ or GDC inside the material, and the percolation threshold of Ni (see Section 3.3.2). 348 For Ni-YSZ prepared by solid-state reaction, the electrical conductivity in air at 25 °C increased with increasing sintering temperature (3936 S cm −1 at 1250 °C and 9203 S cm −1 at 1450 °C) and decreased with an increasing amount of pore former.…”
Section: Lamno 3 !mentioning
confidence: 99%
“…The effect of aging on 40, 50, and 60 wt.% of Ni in 8 mol% YSZ after 500 h of heating has been studied, and it was found that only 40 wt.% Ni-YSZ exhibited a loss of metallic conductivity. In addition, through the sintering process, it has been noticed that electrical conductivity was not affected by the aging process [17].…”
Section: Introductionmentioning
confidence: 99%